2011
DOI: 10.1097/tp.0b013e31821cded7
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Donor Age and Human Leukocyte Antigen Matching in the Setting of Multiple Potential Living Kidney Donors

Abstract: Background Defining living donor (LD)-related risk factors affecting kidney transplant outcome will allow better donor selection and more educated informed consent when there is more than one potential donor. We studied risk factors in a large cohort at a single institution. Methods We reviewed 1632 recipients who underwent LD kidney transplantation at the University of Minnesota between January 1, 1990, and October 1, 2009. Using Cox regression, we studied the effect of donor and recipient risk factors on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Although anti-DP antibodies are frequently detected in sensitized patients, their impact on transplant outcome is still not clear and needs to be further evaluated [117]. In the context of kidney transplantation from live donors, donor age and HLA matching have recently been shown to be independent donor-related risk factors associated with both decreased patient and graft survival [123].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…Although anti-DP antibodies are frequently detected in sensitized patients, their impact on transplant outcome is still not clear and needs to be further evaluated [117]. In the context of kidney transplantation from live donors, donor age and HLA matching have recently been shown to be independent donor-related risk factors associated with both decreased patient and graft survival [123].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…Clinical data have confirmed that matching MHC alleles between donor and host greatly mitigates the risk of immune rejection of transplanted cells or organs (Dunn et al, 2011;Rizzari et al, 2011;Vu et al, 2011;Held et al, 1994). As such, MHC matching plays a crucial role in the acceptance or rejection of any transplanted tissues (Magistris et al, 1992;Buus et al, 1987).…”
Section: Comparative Sequence Identity Of the Major Histocompatibilitmentioning
confidence: 81%
“…Recently, Rizzari et al described a population of 1632 patients with HLA mismatches defined as 0, 1Y2, 3Y4, and 5Y6. A significant effect of HLA mismatches on the risk of graft failure was found in the highest category mismatches (13).…”
Section: Discussionmentioning
confidence: 98%